AMAZÔNICA CHIMERA: ART, MECENATE AND COLLECTING IN BELÉM DO PARÁ, 1890-1910 - Aldrin Moura de Figueiredo (Clio: Revista de Pesquisa Histórica, 2010)
This article analyzes the constitution of the Art market in Belém, Pará (Brazil) during the Belle-époque, between 1890 and 1910. Basing ourselves on the local debates on art and considering the importance of State patronage, we also analyze the process leading to the formation of private art collections as well as public art galleries, the birth of circles of intellectuals specialised in the arts and the historical background that shaped the art of collecting in the state of Pará at the time.